2005
DOI: 10.1242/jeb.01714
|View full text |Cite
|
Sign up to set email alerts
|

A year in the thermal life of a free-ranging herd of springbokAntidorcas marsupialis

Abstract: We used miniature data loggers implanted in the abdominal cavity to measure core body temperatures at 30·min intervals in eight (three males, five females) adult free-ranging springbok Antidorcas marsupialis in their natural habitat, over a period of 11-13 months. The animals were subjected to a nychthemeral range of air temperature that often exceeded 20°C, with an absolute minimum temperature of -6°C and a maximum of 34°C. Abdominal temperature exhibited a low amplitude (~1.2°C) nychthemeral rhythm, with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 30 publications
3
35
3
Order By: Relevance
“…Assuming a body temperature of 37.5-38°C, this represents a decrease in body temperature of about 4°C. Other studies on camels (Camelus dromedarius) and springbok (Antidorcas marsupialis) showed slightly higher daily T b amplitudes exceeding 6 and 7°C, respectively (Schmidt-Nielsen et al, 1967;Fuller et al, 2005). However, the amplitudes shown by our ponies were distinctively higher than the normal circadian variations in body temperature for horses [∆1°C (Piccione et al, 2002a)], so we suggest that our ponies likewise used adaptive heterothermy to reduce energy expenditure, characterized by an increased amplitude of the nychthemeral T b rhythm (Fuller et al, 2005).…”
Section: Research Articlesupporting
confidence: 42%
“…Assuming a body temperature of 37.5-38°C, this represents a decrease in body temperature of about 4°C. Other studies on camels (Camelus dromedarius) and springbok (Antidorcas marsupialis) showed slightly higher daily T b amplitudes exceeding 6 and 7°C, respectively (Schmidt-Nielsen et al, 1967;Fuller et al, 2005). However, the amplitudes shown by our ponies were distinctively higher than the normal circadian variations in body temperature for horses [∆1°C (Piccione et al, 2002a)], so we suggest that our ponies likewise used adaptive heterothermy to reduce energy expenditure, characterized by an increased amplitude of the nychthemeral T b rhythm (Fuller et al, 2005).…”
Section: Research Articlesupporting
confidence: 42%
“…A seasonal change in morning T c and mean 24h T c has also been seen in springbok, a small African antelope (Fuller et al, 2005). Those authors argued that a T c that is lower in winter than in summer might relate to energy availability.…”
Section: Discussionmentioning
confidence: 86%
“…Angilletta et al, 2010). Nevertheless, the reduction of T b at night may improve the ponies' capacity to store heat during hot days and thus reduce the energetic cost for thermoregulation (Fuller et al, 2005;Arnold et al, 2006). This type of adaptive heterothermy has been reported in other ungulates such as eland (Taylor and Lyman, 1967), oryx (Taylor, 1969), giraffe (Langman and Maloiy, 1989) and Thomson's as well as Grant's gazelles (Taylor, 1970).…”
Section: Seasonal Changes In Physiological Parametersmentioning
confidence: 77%